Using donor human milk to feed vulnerable term infants: a case series in KwaZulu Natal, South Africa - Penelope Reimers; Natalie Shenker; Gillian Weaver; Anna Coutsoudis (BMC, 2018)
Abstract Background Donor human milk is the World Health Organization's recommendation for infant feeding when the mother's own breast milk is unavailable. Breast milk has been shown to reduce morbidity and mortality and in low birthweight infants, donor milk reduces the incidence of necrotising enterocolitis, late onset sepsis and improves outcomes. There is a paucity of literature documenting outcomes of using donor human milk in older children who need additional support for a variety of health issues. Case presentation A series of seven case studies is presented of orphaned and abandoned children, many of whom were either HIV exposed or positive. All children were fed with pasteurised donor human milk at a transition home and their progress reported. Conclusions Although detailed medical records were not always available, the case studies provide anecdotal evidence of the protective effects of donor human milk against failure to thrive, diarrhoea, atopic dermatitis, and opportunistic infections.